Kajian Interaksi Obat Pada Peresepan Pasien Diabetes Melitus Di Salah Satu Rumah Sakit Di Kota Bandung - Ameilia Ameilia; Sri Adi Sumiwi (Journal of Pharmaceutical and Sciences, 2023)
Introduction: Drug interactions are events that occur if the use of drugs in a shared time. The drug interactions that occur can produce adverse or beneficial effects. Purpose: to determine the potential interaction of drugs given to outpatients with diabetes mellitus diagnosis in one of the hospitals. Method: the study was conducted using a descriptive analysis design, by collecting retrospective data using prescription documents for diabetic patients in outpatient pharmacy installations in hospitals in the city of Bandung. Results: the study showed that the Biguanida group was often used as much as 82.4% and the interaction of the use of Glimepirid with metformin as many as 25 cases (21.2%) with a moderate level of interaction. Conclusion: The antidiabetic drug that is often used is the Biguanida group with a frequent interaction is Glimepirid with metformin.